Vibration Test and Signal Analysis of RV Reducer - Chen Liguo; Wang Jiugen; Zhang Jing (Jixie chuandong)
RV reducer is a mechanical system,will inevitably yield vibration in its operation process.Three measuring points are arranged on the RV reducer and the vibration signals generated in the work is investigated with the RV reducer test rig and vibration test system. The vibration signals of domestic SHPR-20 E RV reducer under different speed and load are collected and analyzed. Then,the vibration signals are analyzed in time domain and frequency domain. With the signal analysis,the vibration characteristics of the RV reducer can be mastered,which provides the test foundation for the research of RV reducer dynamics study,fault diagnosis and extraction,vibration and noise reduction in the future.